2014
DOI: 10.1186/1476-4598-13-214
|View full text |Cite
|
Sign up to set email alerts
|

Supraphysiological androgen levels induce cellular senescence in human prostate cancer cells through the Src-Akt pathway

Abstract: BackgroundProstate cancer (PCa) is the second leading cause of cancer mortality of men in Western countries. The androgen receptor (AR) and AR-agonists (androgens) are required for the development and progression of the normal prostate as well as PCa. However, it is discussed that in addition to their tumor promoting activity, androgens may also exhibit tumor suppressive effects. A biphasic growth response to androgens a growth-promoting and -inhibition has been observed that suggests that administration of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
133
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(143 citation statements)
references
References 49 publications
10
133
0
Order By: Relevance
“…It was recently reported that p16 can be also regulated by Src-AKT pathway in cellular senescence in human prostate cancer cells [28]. In this study, our result indicated that the phosphorylation levels of FOXO1 and FOXO3a were also markedly increased by the co-treatment when compared to that induced by either Src or mTOR inhibitor alone (Fig 2B).…”
Section: Resultssupporting
confidence: 74%
“…It was recently reported that p16 can be also regulated by Src-AKT pathway in cellular senescence in human prostate cancer cells [28]. In this study, our result indicated that the phosphorylation levels of FOXO1 and FOXO3a were also markedly increased by the co-treatment when compared to that induced by either Src or mTOR inhibitor alone (Fig 2B).…”
Section: Resultssupporting
confidence: 74%
“…Numerous studies demonstrated the pro-senescence activity of the Akt signaling pathway [36-38]. However, the anti-senescence activity of the Akt signaling pathway has also been proposed in several types of tissues and cells, such as multipotent mesenchymal stem cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the concentration, androgens can promote as well as suppress cell proliferation through the regulation of the androgen receptor (AR) [49]. For example, cellular senescence is a natural mechanism to suppress malignant cell growth through the regulation of various tumor suppressor proteins [913].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the concentration, androgens can promote as well as suppress cell proliferation through the regulation of the androgen receptor (AR) [49]. For example, cellular senescence is a natural mechanism to suppress malignant cell growth through the regulation of various tumor suppressor proteins [913]. In addition, exogenous and endogenous stimuli cause irreversible cell cycle arrest leading to morphological changes and altered gene expression [14, 15].…”
Section: Introductionmentioning
confidence: 99%